The disappearance and return of nanoparticles upon low energy ion irradiation - Choupanian, Shiva; Nagel, Alessandro; Moeller, Wolfhard; Pacholski, Claudia; Ronning, Carsten (Nanotechnology, 2022)
Ion irradiation of bulk and thin film materials is tightly connected to well described effects such as sputtering or/and ion beam mixing. However, when a nanoparticle is ion irradiated and the ion range is comparable to the nanoparticle size, these effects are to be reconsidered essentially. This study investigates the morphology changes of silver nanoparticles on top of silicon substrates, being irradiated with Ga+ ions in an energy range from 1 to 30 keV. The hemispherical shaped nanoparticles become conical due to an enhanced and curvature-dependent sputtering, before they finally disappear. The sputter yield and morphology changes can be well described by 3D Monte Carlo TRI3DYN simulations. However, the combination of sputtering, ion beam mixing, ion beam induced diffusion, and Ostwald ripening at ion energies lower than 8 keV results in the reappearance of new particles. These newly formed nanoparticles appear in various structures depending on the material and ion energy.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Ag nanoparticles; Ion beam mixing; Ion-nanoparticle interaction; Ostwald ripening; Phase sepereation; Sputtering; TRI3DYN